Milder symptoms and shorter course in patients with re-positive COVID-19: A cohort of 180 patients from Northeast China - Li, Hongyan; Zhu, Mingqin; Zhang, Peng; Yan, Xingjian; Niu, Junqi; Wang, Zhenyu; Cao, Jie (Frontiers in Microbiology, 2022)
China experienced another widespread Corona Virus Disease 2019 (COVID-19) outbreak recently caused by omicron variant, which is less severe but extremely contagious compared to other COVID-19 variants, causing enormous efforts for local government to eliminate the spreading of the disease. Previous studies showed that after ‘recovering’ from the virus, some patients could re-positive for nucleic acid test, causing great challenge to control the disease spreading. In this study, we aim to analyze the clinical and laboratory characteristics of re-positive COVID-19 patients from north east China. We retrospectively analyzed data from Corona Virus nucleic acid RT-PCR re-positive COVID-19 patients who were admitted to The First Hospital of Jilin University, Jilin Province, China from March to June 2022. Detailed clinical symptoms, medical history, anti-Corona Virus (CoV) IgG, IgM levels and CoV nucleic acid Ct values during the re-positive period were collected and analyzed. A total of 180 patients were included in this study, including 62 asymptomatic cases and 118 mild cases. The cohort included 113 males and 67 females, the average age was 45.73 years old. The median time between recovering from the virus to re-positive was 13 days. Our results showed that the proportion of re-positive patients with symptoms were lower and the nucleic acid test positive duration were shorter during the re-positive period. Furthermore, the proportion of patients with symptoms were higher in those who had underlying disease, the anti-CoV IgG levels were lower, and total disease duration were longer in patients with underlying disease. In conclusion, symptoms are milder and the CoV nucleic acid test positive course were shorter during the re-positive period. Concomitant underlying disease is an important factor associated with clinical symptoms and overall course of COVID-19 re-positive patients and may be associated with lower anti-CoV IgG levels. Large-scale and multi-center studies are recommended to better understand the pathophysiology of the recurrence of patients with COVID-19.